PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP PERUBAHAN KUALITAS TIDUR PEREMPUAN MENOPAUSE - Italia (LPPM STIKes Mitra Adiguna, 2024)
Menopause is a permanent cessation of menstruation caused by ovarian failure. It can be diagnosed within the year of the last menstrual period and is retrospective. The period leading to these changes is also called perimenopause. This is characterized by biological and endocrine changes that cause symptoms and irregular bleeding. Progressive muscle relaxation is the use of techniques to encourage and obtain relaxation for the purpose of reducing signs and symptoms such as pain, muscle stiffness and anxiety. Physiologically progressive muscle relaxation reduces oxygen consumption, respiratory metabolic rate, muscle tension, premature ventricular contractions, systolic and diastolic blood pressure, increases brain alpha waves. The method of this research is Using a quantitative design in this research used a pre-experimental design with a one group pre-post test approach. Where in this study the sample was given a pre-test (initial observation) before being given the intervention, after that the intervention was given, then a post-test (final observation) was carried out. The results of the t-test in the study were 14,038 with a significance of 0.000 (p value 0.05). This means that progressive muscle relaxation therapy has a significant effect on the sleep quality of menopausal women. The results of this research can be used as reference material and add to the literature at STIKES Mitra Adiguna Palembang, especially journals and materials that support the writing of scientific papers related to the sleep quality of menopausal women.